2015
DOI: 10.15623/ijret.2015.0407063
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Wastewater From Chrome Plating Industry by Ion Exchange Method

Abstract: In the present work an attempt has been made to evaluate the efficiency of removal Cr(VI) from chrome plating industry wastewater by using fresh and reconditioned strong base anion exchanger Tulsion A-27(MP). The Experimental data is evaluated by plotting breakthrough curves and by employing Bohart-Adams Model. The maximum removal (80%) of Cr(VI) from plating wastewater is obtained at 14cm column bed height and flowrate 1mL/min for 1144.39mg/L of influent Cr(VI) concentration. The breakthrough curves for recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Hexavalent chromium (Cr(Ⅵ)) is a well‐known pollutant that originates from effluents of several industrial processes such as tanning, electroplating, dyeing, and wood preservation (WHO, 2013). In industrial wastewaters, high chromium concentrations were found in tannery effluents (0.7–345 mg/L) (Dhungana & Yadav, 2009), textile mill effluents (0.11–0.21 mg/L) (Bhardwaj et al, 2014), and chrome plating industry wastewater (5722 mg/L) (Karegar et al, 2015). For natural waters, lower chromium concentrations have been described; for example, 0.1–117 μg/L in freshwater and 0.2–50 μg/L in seawater (Shanker & Venkateswarlu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hexavalent chromium (Cr(Ⅵ)) is a well‐known pollutant that originates from effluents of several industrial processes such as tanning, electroplating, dyeing, and wood preservation (WHO, 2013). In industrial wastewaters, high chromium concentrations were found in tannery effluents (0.7–345 mg/L) (Dhungana & Yadav, 2009), textile mill effluents (0.11–0.21 mg/L) (Bhardwaj et al, 2014), and chrome plating industry wastewater (5722 mg/L) (Karegar et al, 2015). For natural waters, lower chromium concentrations have been described; for example, 0.1–117 μg/L in freshwater and 0.2–50 μg/L in seawater (Shanker & Venkateswarlu, 2011).…”
Section: Introductionmentioning
confidence: 99%